Analysis of the Decision-Makers' Profile when Making Decisions in Logistics. Issue 3 (2nd October 2017) - Soares Iwamoto, Henrique; Vidal Vieira, José Geraldo; Ubeda, Cristina Lourenço; Laiate Liesack, Maria Luisa
ABSTRACT: This article aims to analyze how personal characteristics relate to decision-making style, considering the cultural environment in logistics decisions. This empirical research is tested using descriptive statistics, Cronbach's Alpha and nonparametric correlation with 49 logistics decision-makers who work in manufacturing and service sectors. Results show that top managers' representatives bear the following characteristics: higher openness to new experiences, goal and accomplishment orientation, greater agreeableness (being easy to deal with on a daily basis), high risk aversion, and elevated spontaneity. In addition, top managers bore lower emotional involvement, and deliberated less in decisions.